Global burden of childhood epilepsy, intellectual disability, and sensory impairments - Olusanya, BO; Wright, SM; Nair, MKC; Boo, N-Y; Halpern, R; Kuper, H; Abubakar, AA; Almasri, NA; Arabloo, J; Arora, NK; Backhaus, S; Newton, CRJ; et al. (American Academy of Pediatrics, 2020)
BACKGROUND: Estimates of children and adolescents with disabilities worldwide are needed to inform global intervention under the disability-inclusive provisions of the Sustainable Development Goals. We sought to update the most widely reported estimate of 93 million children <15 years with disabilities from the Global Burden of Disease Study 2004.